Family Financial Socialization : Impact of Scholarship Payments on Research Scholarsâ€™ Financial Behaviour and Financial Well-Being - Anita; Kochhar, Khyati (Indian Journal of Finance, 2024)
Purpose : The fundamental purpose of this research study was to describe and test a conceptual correlation between â€œfinancial behaviorâ€ (FB) and â€œfinancial well-beingâ€ (FWB) using the scholarship payments of research scholars. The study particularized how scholarship payment impacted financial behaviour and how financial behaviour affected the financial well-being of scholars. Design/Methodology/Approach : Data (N = 94) was collected by an offline survey conducted at Banasthali Vidyapith, a fully residential womenâ€™s university. By using a detailed self-structured questionnaire, primary data was obtained. From the target population of 300, the sample size of 150 scholars was taken through convenience sampling. Descriptive analysis, bivariate correlation, and linear regression were used with the aid of SPSS software to infer outcomes. Findings : This study stated that in the â€œFamily Financial Socializationâ€ (FFS) model, scholarship payment was not the only factor affecting research scholarsâ€™ financial behaviour. It means that they are not financially independent with scholarship payments. Furthermore, good and risky financial behaviour ensured a picture of financial well-being in life. So, in research scholarsâ€™ lives, the mostly financial role was played by their parents, and with their help, they choose to use good financial behaviour, which resulted in financial well-being in the future. Originality/Value : This kind of research is the first to examine the relationship between financial behavior and financial well-being using the scholarship payments of research scholars based on family financial socialization theory.